1972
DOI: 10.1177/002221947200500305
|View full text |Cite
|
Sign up to set email alerts
|

A Comparsion of Figure Drawings and WISC IQ's Among Disabled Readers

Abstract: Children's figure drawings have been used as a measure of intellectual development since at least the 1920's. This study assesses the relationship between IQ scores from two systems for scoring figure drawings as compared to performance on the WISC in a population of disabled readers. The two figure drawing scoring systems yield very similar results in spite of the fact that one was more recently standardized and is more complex. Scores derived from figure drawings show significant correlations with scores fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1973
1973
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Criterion validity correlates significantly (2_< .01) with other cognitive measures. (Also see Laosa, Swartz & Holtzman, 1973;Pikulski, 1972;Goodenough, 1926;Harris, 1963;Miljkovitch & Landry, 1984;Havighurst, Gunther & Pratt, 1946. ) 3.…”
Section: Instrumentsmentioning
confidence: 99%
“…Criterion validity correlates significantly (2_< .01) with other cognitive measures. (Also see Laosa, Swartz & Holtzman, 1973;Pikulski, 1972;Goodenough, 1926;Harris, 1963;Miljkovitch & Landry, 1984;Havighurst, Gunther & Pratt, 1946. ) 3.…”
Section: Instrumentsmentioning
confidence: 99%
“…Of the 10 studies in this area, only two included GH scores of normal controls: Colligan (1967) reported significantly lower GH scores for low-achieving boys, despite California Test of Mental Maturity scores comparable with those of a group of normal boys, and Hartman (1972) reported GH scores that appeared to be comparable for normal and learning-disabled children, but no tests of significance were reported. Discrepancies between the GH scores of the learning disabled and criterion scores on measures such as the WISC-R have been attributed to such factors as preceptual-motor incoordination, anxiety, impulsivity (Pikulski, 1972), and maturational lag (Ingram, Mason, & Blackburn, 1970), when they might be more parsimoniously explained in terms of the upward bias in the Harris standardization sample, which produces discrepant GH/criterion scores in both normal and special populations. Deficiencies in body image and self-concept thought to be associated with learning problems have been investigated thr.ough GH performance in a number of studies.…”
Section: Learning Disabilitiesmentioning
confidence: 99%
“…Two of three studies (Levine & Gross, 1968;Pikulski, 1972;Vane, 1967) that included DAM scores as well as GH scores found that the Goodenough DAM scores were significantly closer to the criterion scores than were the GH scores. The greater power of the DAM as an estimator of criterion scores suggests that the approximate 10-point upward bias in Harris's norms may partially account for these discrepancies.…”
Section: Criterion Validitymentioning
confidence: 99%
“…The pupils' comprehension level using cloze test could be characterized as struggling because of the nature and structure of the test requiring exact replacements to fill in the blanks. Pikulski and Tobin (1982) recommended to establish functional reading levels of students. Vacca and Vacca (1989) also explained that the criteria for the cloze test were established from the purview of exact word replacements.…”
Section: Comprehension Level and Test Typesmentioning
confidence: 99%
“…Cloze test, as defined by Harris and Smith (1986), is derived from "closure" which refers to filling in or completing pictures, sentences, or stimuli. Pikulski and Tobin (1982) suggested that most researchers are using cloze test with exact replacements to establish functional reading levels (independent, instructional, frustration), and to determine the grade level or difficulty of texts and evaluate content materials. Additionally, checking the exact replacements for cloze test is quick and efficient since only one answer is considered correct; hence, inter-reliability is already guaranteed.…”
Section: Introductionmentioning
confidence: 99%